O gênero masculino e os cuidados de saúde: a experiência de homens de um centro de saúde - Bertolini, Daniele Natália Pacharone; Simonetti, Janete Pessuto (Universidade Federal do Rio de Janeiro, 2014)
The aim was to understand how the men of a Health Center behave concerning health care. Qualitative study in a Center for School Health that selected by convenience and interviewed 15 individuals that were adults of male gender and the data organized according to the Discourse of the Collective Subject. Four central ideas emerged that portray the reasons for seeking the service, health problems, attitudes towards these issues and participation in the activities of the unit. These individuals are assiduous, care to follow the advice received and used the individual attention, preferably, for lack of time, but show an interest in participating in group activities. This should be used by the services as an opportunity to enhance their participation in specific groups that are already existing for men, offering a welcome space and offer listening to several problems, being a form of reintegration of these individuals with the health service.

Compreender como os homens de um Centro de Saúde se comportam quanto aos cuidados com a saúde. Estudo qualitativo, realizado em um Centro de Saúde Escola que selecionou por conveniência e entrevistou 15 indivíduos do gênero masculino, adultos e organizou os dados conforme o Discurso do Sujeito Coletivo. Emergiram quatro ideias centrais que retratam os motivos para procurar o serviço, problemas de saúde, atitudes diante desses problemas e participação nas atividades da unidade. Esses indivíduos são assíduos, se preocupam em seguir as recomendações recebidas e utilizam o atendimento individual, preferencialmente, por falta de tempo, mas demonstram interesse em participar de atividades em grupo. Isto deve ser utilizado pelo serviço como oportunidade de intensificar a participação deles em grupo específico já existente para homens, que oferece um espaço de acolhimento e escuta de problemas diversos, sendo uma forma de reintegração desses indivíduos junto ao serviço de saúde.

El estudio buscó comprender cómo los hombres de un Centro de Salud se comportan cuanto a los cuidados con la salud. Investigación cualitativa, realizada en un Centro de Salud que seleccionó y entrevistó, por conveniencia, a 15 hombres adultos y organizó los datos de acuerdo con el Discurso del Sujeto Colectivo. Emergieron cuatro ideas centrales que retratan las razones para la presencia del hombre en el servicio: problemas de salud, actitudes delante de estas cuestiones; y participación en las actividades. Son asiduos, se preocupan en seguir las recomendaciones recibidas y utilizan la atención individual, preferencialmente, por falta de tiempo, pero muestran interés en participar en actividades de grupo. Esto puede ser usado como una oportunidad para mejorar su participación en el grupo específico para los hombres, que ofrece un espacio para recibir y escuchar a problemas diversos, siendo una forma de reinserción de estas personas con el servicio de salud.
El género masculino y los cuidados de salud: la experiencia de hombres en un centro de salud
The male genre and health care: the experience of men at a health center
Keywords: Saúde do Homem; Centros de Saúde; Enfermagem; Assistência à Saúde; Men's Health; Health Centers; Nursing; Delivery of Health Care